Improving weekend handover in a teaching hospital elective general surgery department - Dexter, Eloise; Walshaw, Josephine; Brown, Ayla; Nadeem, Tehmina; Yiasemidou, Marina; Lo, Terence (Frontiers in Surgery, 2023)
Effective documentation and transfer of clinical information are vital for the continuity of care, patient safety, and maintaining medico-legal records, as outlined by the Royal College of Surgeons 'Safe Handover: Guidance from the Working Time Directive working party'. Our elective surgery weekend team cross-covers both Colorectal and Upper Gastrointestinal surgical specialties across multiple wards, which poses a significant challenge. The aim of this study was to improve the documentation of patients' weekend plans through the introduction of a weekend handover proforma. We reviewed the weekend plans of 199 patients overall. 41 records were initially reviewed over a 2-week period. The surgical multidisciplinary team was then surveyed to establish the need for an improved weekend handover. Following this, a weekend handover proforma was introduced as part of the Friday ward round and education on the expectations were provided at a local Surgery Clinical Governance meeting. The documentation of the weekend plan was reviewed for 158 patients over a 6-week period and a post-intervention survey was disseminated.The preliminary survey highlighted concerns for delayed discharges and patient safety over the weekend, with 88.2% of respondents agreeing a weekend handover proforma would be beneficial. The initial data confirmed inadequate documentation of diagnosis (19.5%), operation/procedure (28.1%), and weekend plans for blood tests (19.5%), discharge planning (2.4%), diet (46.3%), antibiotics (19.5%), intravenous (IV) fluids (22.0%), mobility (19.5%) and drain/wound care (37.5%). After education and implementing a weekend handover proforma, these results increased for documentation of diagnosis (61.2%), operation/procedure (83.2%), blood tests (59.7%), and discharge planning (85.8%). However, there was little improvement in diet (53.0%) and no improvement in the weekend plans for antibiotics (14.2%), IV fluids (17.2%), mobility (14.9%) and drain/wound care (20.2%). The postintervention survey showed an improvement across all areas, notably continuity of care and patient safety, with 95.5% of individuals finding the weekend handover proforma aided in patient care over the weekend. Education of the ward team and implementation of a weekend handover proforma resulted in a marked improvement in the documentation of patients' weekend plans, which is essential to ensure the continuation of safe and effective patient care.